The Work Engagement as a Mediator between Workload, Work Environment, and Generation Z Job Performance - Akbar Fahrurrohman Fiqanda Cuseno Romi; Mariana Puspa Dewi (Journal of Educational Management Research, 2026)
This study aims to examine the mediating role of work engagement in the relationship between workload, work environment, and Generation Z employee performance. A quantitative approach was employed using purposive sampling, involving 100 Generation Z employees working in the service sector. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The analysis procedures included tests of construct validity and reliability, structural model evaluation, and mediation analysis using the bootstrapping method. The results indicate that workload and work environment have positive and significant effects on Generation Z employee performance. The work environment also shows a significant positive effect on work engagement, whereas the effect of workload on work engagement is moderate. Furthermore, work engagement partially mediates the relationship between work environment and employee performance but does not mediate the effect of workload on performance. The R² value of 0.649 demonstrates that the proposed model explains 64.9% of the variance in Generation Z employee performance. These findings highlight the importance of fostering a supportive work environment and managing workload effectively to enhance work engagement and performance among Generation Z employees.